2010
DOI: 10.1111/j.1600-0463.2010.02658.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of mismatch repair genes (hMSH2 and hMLH1) in hepatocellular carcinoma in Egypt

Abstract: Egypt has the highest prevalence rate of hepatitis C virus (HCV) infection in the world. HCV contributes to the development of about 70% of hepatocellular carcinoma (HCC) cases. Understanding the molecular basis of hepatocarcinogenesis is important for planning the therapeutic regimen for HCC patients. To clarify the possible role of mismatch repair (MMR) genes in HCV-related HCC, we studied 50 HCV-related HCC specimens (28 of which were with adjacent non-cancerous cirrhotic liver tissue, ANCLT) and 30 specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Overexpression of two key genes involved in the early steps of the NER process, ERCC1 and XPC, is associated with liver fibrogenesis and cancer and could be related to the well-recognized resistance of HCC to chemotherapeutics [135]. Several studies have revealed multiple genetic alterations of the mismatch repair (MMR) genes in hepatocarcinogenesis [136]. Among the MMR genes, human Mut L homologues 1 and 2 (hMLH1 and hMSH2) play important roles in DNA repair [137139].…”
Section: The Impact Of Ddr Pathways On Hcc Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of two key genes involved in the early steps of the NER process, ERCC1 and XPC, is associated with liver fibrogenesis and cancer and could be related to the well-recognized resistance of HCC to chemotherapeutics [135]. Several studies have revealed multiple genetic alterations of the mismatch repair (MMR) genes in hepatocarcinogenesis [136]. Among the MMR genes, human Mut L homologues 1 and 2 (hMLH1 and hMSH2) play important roles in DNA repair [137139].…”
Section: The Impact Of Ddr Pathways On Hcc Developmentmentioning
confidence: 99%
“…Reduced expression of hMSH2 and hMLH1 in both HCC and ANCLT suggests that this event occurs at early stages of HCV-related hepatocarcinogenesis. Moreover, the significant association between reduced expression of both MMR genes and poor histologic grades of the tumor claims that these proteins are involved in the process of cancer progression [136]. …”
Section: The Impact Of Ddr Pathways On Hcc Developmentmentioning
confidence: 99%
“…However, we detected promoter methylation not only in tumour but also in non-tumour adjacent tissue. In line with this, Helal et al detected reduced MLH1 and MSH2 expression in HCCs but also in adjacent non-cancerous surrounding tissues [22]. Possibly, the used tumour surrounding tissue already contained precancerous cells in some cases which might be detectable by high sensitive MSP analysis.…”
Section: Discussionmentioning
confidence: 80%
“…Others described the influence of HCV on DNA methyltransferase 1 [25], [26] a protein essential for the regulation of MLH1 and MSH2 expression [27]. Since chronic HCV infection is a major risk factor for HCC and HCC samples of HCV infected patients were only [22] or most dominantly analysed [8], [24] in the cited publications we rather hypothesize that promoter methylation of MMR proteins and p16 is frequently occurring during HCC progression in general without close connection to HCV.…”
Section: Discussionmentioning
confidence: 90%
“…Genomic instability is an early and important event in carcinogenesis. Changes such as microsatellite instability and hypermethylation in the promoter regions of the hMLH1 and hMSH2 genes are detected frequently in potentially malignant lesions and cancer . Knowledge of the histological features and pathogenesis of lip lesions such as AC and SCC is important for the early diagnosis and correct treatment of these lesions.…”
Section: Introductionmentioning
confidence: 99%